Endobronchial metastasis from resected renal cell carcinoma causing total lung collapse - Liam, C.K.; Poh, M.E.; Pang, Y.K.; Chua, K.T. (John Wiley & Sons Ltd, 2013)
We report a man presenting with dyspnea, cough, and hemoptysis due to left lung collapse from an endobronchial tumor obstructing the left main bronchus. Endobronchial biopsy of the tumor showed renal cell carcinoma, identical to a previous specimen of renal cell carcinoma removed by a radical left nephrectomy five years ago. The endobronchial tumor was removed by snare diathermy through a flexible bronchoscope, following which his symptoms resolved and the left lung re-expanded. Endobronchial metastasis from renal cell carcinoma is rare and can mimic obstruction from other endobronchial etiologies, such as bronchogenic carcinoma. Total lung collapse as a result is even more uncommon, although atelectasis is well described. Endobronchial techniques, such as snare diathermy, can relieve obstruction, providing symptom palliation even in advanced disease.